Diet, Sports, and Psychological Stress as Modulators of Breast Cancer Risk: Focus on OPRM1 Methylation - Li, Liangliang; Li, Shuo; Qin, Shidong; Gao, Yu; Wang, Chao; Du, Jinghang; Zhang, Nannan; Chen, Yanbo; Han, Zhen; Yu, Yue; Wang, Fan; Zhao, Yashuang (Frontiers in Nutrition, 2021)
Background: DNA methylation is influenced by environmental factors and contributes to adverse modification of cancer risk and clinicopathological features. Methods: A case-control study (402 newly diagnosed cases, 470 controls) was conducted to evaluate the effect of environmental factors and OPRM1 methylation in peripheral blood leukocyte (PBL) DNA on the risk of breast cancer. A case-only study (373 cases) was designed to evaluate the effects of environmental factors on OPRM1 methylation in tumor tissue and the relationship of methylation with clinicopathological features. Results: We found a significant association between hypermethylation of OPRM1 and the risk of breast cancer (OR = 1.914, 95%CI = 1.357–2.777). OPRM1 hypermethylation in PBL DNA combined with low intake of vegetable, garlic, soybean, poultry, and milk; high pork intake; less regular sports and a high psychological stress index significantly increased the risk of breast cancer. Soybean intake (OR = 0.425, 95%CI: 0.231–0.781) and regular sports (OR = 0.624, 95%CI: 0.399–0.976) were associated with OPRM1 hypermethylation in tumor DNA. OPRM1 hypermethylation in tumor tissue was correlated with estrogen receptor (ER) (OR = 1.945, 95%CI: 1.262–2.996) and progesterone receptor (PR) (OR = 1.611, 95%CI: 1.069–2.427) negative status; in addition, OPRM1 hypermethylation in PBL DNA was associated with human epidermal growth factor receptor 2 (HER-2) negative status (OR = 3.673, 95%CI: 1.411–9.564). Conclusion: A healthy diet, psychosocial adaptability, and regular sports are very beneficial for breast cancer prevention and progress, especially for OPRM1 hypermethylation carriers. Personalized treatment considering the correlation between OPRM1 hypermethylation and ER and PR status may provide a novel benefit for breast cancer patients.